Clinical Validation of SensiTest Colistin, a Broth Microdilution-Based Method To Evaluate Colistin MICs - Carretto, Edoardo; Brovarone, Flavia; Russello, Giuseppe; Nardini, Paola; El-Bouseary, Maisra M.; Aboklaish, Ali F.; Walsh, Timothy R.; Tyrrell, Jonathan M. (Journal of clinical microbiology, 2018)
The global spread of multidrug-resistant Gram-negative bacteria has led to the return of colistin for treating severe infections. Recently, different plasmid-mediated genes conferring resistance to this drug were described and reported worldwide. International committees (EUCAST/CLSI) reevaluated inconsistencies surrounding colistin antimicrobial susceptibility testing (AST), concluding that broth microdilution (BMD) should serve as the reference method for AST. The development of an accurate, reproducible commercial test based on BMD is therefore highly desirable. SensiTest Colistin (STC), a BMD-based compact 4-test panel containing the lyophilized antibiotic in 7 2-fold dilutions (0.25 to 16 μg/ml) was here compared with the EUCAST-CLSI standard reference method (BMD) and, for some isolates, with the automated Phoenix 100 system (PHX). A total of 353 bacterial strains were evaluated by two different laboratories; 137 isolates were resistant to colistin (19 were intrinsically resistant, 83 harbored the mcr-1 gene). Essential agreement (EA) between STC and BMD was obtained for 339 out of the 353 strains tested (96.0%). Overall categorical agreement was obtained for 349 out of the 353 strains analyzed (98.9%). Two major errors (MEs; 0.93%) and two very major errors (VMEs; 1.46%) were documented. STC appeared to be a simple but highly reliable test with good reproducibility even with panels stored at room temperature or at 35°C. Moreover, STC showed a good performance with strains carrying the mcr-1 gene, with a 98.8% EA. As the secondary endpoint of our study, VMEs for PHX were documented for 6 isolates (10%).